2014
DOI: 10.1007/7854_2014_296
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Correlates of Premenstrual Dysphoric Disorder (PMDD)

Abstract: Premenstrual dysphoric disorder (PMDD) is a mood disorder with onset of functionally impairing or distressing mood symptoms in the late luteal phase of the menstrual cycle. Psychophysiologic findings in PMDD broadly fall into two categories: vulnerability trait findings, thus categorized because they are present in the asymptomatic phases of the menstrual cycle, and state findings, which are only present in the symptomatic late luteal phase and which are potentially representative of the hormonal events and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…Variation in menstrual cycle effects could be addressed in future studies by imaging female participants at a specific menstrual cycle phase (Witte et al 2010), or by exclusively enrolling either women who are or those who are not taking oral contraceptives. Alternatively, counterbalanced, longitudinal crossover designs, where subjects serve as their own controls, could be employed to address this issue (Poromaa 2014). Most practical, however, might be determination of menstrual cycle phase at the time of imaging, which can then be considered as a regressor during data analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in menstrual cycle effects could be addressed in future studies by imaging female participants at a specific menstrual cycle phase (Witte et al 2010), or by exclusively enrolling either women who are or those who are not taking oral contraceptives. Alternatively, counterbalanced, longitudinal crossover designs, where subjects serve as their own controls, could be employed to address this issue (Poromaa 2014). Most practical, however, might be determination of menstrual cycle phase at the time of imaging, which can then be considered as a regressor during data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Functional neuroimaging has been employed to assess the impact of ovarian sex hormones on cortical function in healthy female animals (Chen et al 2009), healthy women (Dreher et al 2007; Schoning et al 2007), and in human disease states such as premenstrual dysphoric disorder (PMDD) (Poromaa 2014; Protopopescu et al 2008b). Functional, but not structural, imaging studies of women across hormonal transitions have recently been extensively reviewed (Peper et al 2011; Sacher et al 2013; Toffoletto et al 2014), and will therefore provide context, but not be the focus of this review.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that "trait" fi ndings in these women occur in the asymptomatic phases of the menstrual cycle and physiologically exhibited trait vulnerability markers include diminished cardiovascular stress responses, lower P300 amplitude, and lower heart rate variability refl ecting increased vagal tone. These fi ndings suggest that women with PMDD share physiological correlates with women with anxiety and depression (Poromaa 2014 ).…”
Section: Premenstrual Dysphoric Disorder (Pmdd)mentioning
confidence: 84%
“…Poromaa ( 2014 ) found that in individuals with PMDD, "state" symptoms occur in the luteal phase, suggesting that women with PMDD have altered luteal phase emotion processing and lower pre-pulse inhibition in the late luteal phase, which could refl ect ovarian steroid-infl uenced altered serotonergic neurotransmission. They suggested that "trait" fi ndings in these women occur in the asymptomatic phases of the menstrual cycle and physiologically exhibited trait vulnerability markers include diminished cardiovascular stress responses, lower P300 amplitude, and lower heart rate variability refl ecting increased vagal tone.…”
Section: Premenstrual Dysphoric Disorder (Pmdd)mentioning
confidence: 99%
“…Lower prepulse inhibition in the late luteal phase may be an important ovarian steroid-influenced indicative of altered serotonergic neurotransmission, of relevance for women with PMDD. Attempts to determine the neural correlates of emotion processing in the late luteal phase are thus far inconsistent, but promising (1).…”
Section: Introductionmentioning
confidence: 99%